PEMBERDAYAAN ANGGOTA PKK KELURAHAN GENTAN SUKOHARJO - Vanda, Yoiceta; Ratnaningsih, Rahajeng; Cahyono, Setyawan Ary (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2015)
The craft of knitted is a product knitted handicrafts hand performed manually, Not a bit of fashion products are made from knitted results, such as suits, shorts, scarves, sweeter, accessories, bags, and other products. Based on the problems faced by partner, required a method of the approach which has been agreed upon between parties college and the partner, namely : 1) Internet trainning, for the management of raw materials by means of the internet, providing training in order to be able to order raw materials are hard to come by, via the internet, 2) Double-knitt training for PKK, this training is intended to be able to acquire human resources who can knit properly, 3) Create Website, this website used to display a model/design knitted and the way of order. There are some activities already axecute on program IbM Pondok Baru Gentan, Sukoharjo, is as follows :1) Knitting training, Training will be  followed by PKK women, the number of participants 17 people. With the materials of  training are : a)  Introduction to the technique of knitting : knitting crafts, chrochet methods, b) Advance knitting Techniques, the method comprising brien knitting.2) Internet and Management Website Training. Training followed by 6 participants. With the materials of training as follows : a) Internet workshop. Includes : the internet, browsing, email, and social networking, b) Management Website includes : introduction page administrator consisting of the main menu, web modul and web admin.